UNDERSTANDING THE SOUND CHARACTER OF THE TOOL WITH A VIDEO SLIDE SKETCH ON THE ENSEMBLE LEARNING AT SMPN14 PADANG - Yos Sudarman; Harisnal Hadi (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2018)
This research aims to develop the subject matter of Art of Culture according to the curriculum of 2013, especially from the enriching aspect of instructional material of musical ensemble. The method used in this research is R & D method. The result of the research has created the development of teaching materials of local musical ensemble on Minangkabau music material, which by displaying the character of the ensemble instrument sound in the form of sketch-based video, the teacher can complete the teaching material in the show and not need to be demonstrated. With the enrichment of musical ensemble lesson material using this sketch-based slide video also, the teacher can present the lesson with more appreciative and attract the attention of the student, that is by the use of materials, tools, materials and study time effectively and efficiently.Keywords: sound character, music tool,video slide sketch, ensemble MEMAHAMI KARAKTER BUNYI ALAT DENGAN VIDEO SLIDE SKETSA PADA PEMBELAJARAN ENSAMBEL DI SMPN14 PADANGPenelitian ini bertujuan untuk mengembangkan materi pelajaran Seni Budaya sesuai kurikulum 2013, khususnya dari aspek memperkaya substansi bahan ajar ensambel musik. Metode yang digunakan dalam penelitian ini adalah metode R&D. Hasil penelitian telah menciptakan pengembangan bahan ajar ensambel musik daerah setempat pada materi musik Minangkabau, yang mana dengan menampilkan karakter bunyi alat musik ensambel dalam bentuk video berbasis sketsa, guru dapat melengkapi bahan ajarnya dalam tayangan dan tidak perlu didonstrasikan. Dengan adanya pengayaan materi pelajaran ensambel musik menggunakan video berbasis slide sketsa ini pula, guru dapat mempresentasikan pembelajaran dengan lebih apresiatif dan menarik perhatian siswa, yakni dengan penggunaan materi, alat, bahan dan waktu belajar yang efektif dan efisien.Kata kunci: karakter bunyi, alat, video slide sketsa, ensamble